Memory - Tortell, Philippe Daniel, 1972-; Turin, Mark; Young, Margot (Peter Wall Institute for Advanced Studies, 2018)
This collection of essays asks readers to think critically, creatively, and broadly about how, why, and when we remember, at a time when the idea of memory - through the commemoration of the First World War - is at the forefront of public discourse.